1937
DOI: 10.1172/jci100899
|View full text |Cite
|
Sign up to set email alerts
|

The Coagulation Defect in Hemophilia. The Effect in Hemophilia of Intramuscular Administration. Of a Globulin Substance Derived From Normal Human Plasma 1

Abstract: The recent investigations of Patek and Stetson (1) 2 indicate that the defect in coagulation of blood in hemophilia resides in the plasma rather than in the platelets. Patek and Taylor (2, 3) 2 isolated a substance from citrated normal cellularfree plasma, by isoelectric precipitation, with which was associated the clot-promoting factor of normal plasma. This substance was effective, both in vitro and after intravenous injection, in reducing the coagulation time of hemophilic blood. By the same method, a simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

1939
1939
2003
2003

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 7 publications
0
33
0
Order By: Relevance
“…A comparison of these data with those previously published for multiple injections of unmodified normal human plasma (10) shows a close correspondence. The maintenance of a lowered coagulation time by repeated injections of unmodified plasma and preparations of plasma free from prothrombin and fibrinogen is in sharp contrast to the refractory phase reported as accompanying multiple injections of acid-precipitated " globulin substance " (3).…”
Section: Methodsmentioning
confidence: 82%
“…A comparison of these data with those previously published for multiple injections of unmodified normal human plasma (10) shows a close correspondence. The maintenance of a lowered coagulation time by repeated injections of unmodified plasma and preparations of plasma free from prothrombin and fibrinogen is in sharp contrast to the refractory phase reported as accompanying multiple injections of acid-precipitated " globulin substance " (3).…”
Section: Methodsmentioning
confidence: 82%
“…During the past two years a study of the nature of " globulin substance " prepared by dilution and acid precipitation of plasma has been made (3,4,5). It was determined that the protein precipitates obtained between pH 5.5 and 6.0 are associated with the largest proportion of clot-promoting activity.…”
mentioning
confidence: 99%
“…Advances in the treatment of haemophilia with antihaemophilic factor began with pioneering work by Patek and Taylor (1937) when they demonstrated that this clot-promoting substance for haemophilic blood found in normal plasma was a protein ('globulin precipitate'). Pohle and Taylor (1937) first demonstrated that intramuscular use of this globulin substance was effective in correcting the clotting time in patients with haemophilia, but also demonstrated the refractory state induced by subsequent injections. The Thorndike also participated in the beginnings of the modern understanding of disseminated intravascular coagulation when Lozner and Taylor (1942) reported the effects of artificial surfaces on the initiation of coagulation and Tagnon et al (1942) studied the fibrinolytic activity of plasma.…”
Section: Coagulationmentioning
confidence: 99%